Using Social Media for Marketing Library Services in Libraries of Iran, Tehran, and Shahid Beheshti Medical Universities - Panahi, Sirous; Roostaei* , Nahid; Nemati-Anaraki, Leila (Journal of Medical Library and Information Science, 2021)
Introduction: The use of social media for marketing library services of academic libraries is growing day by day. The purpose of this study is to investigate the use of social media in marketing services of libraries of Iran, Tehran and Shahid-Beheshti universities of medical sciences. Methods: The study used a survey method. The questionnaire was used for data collection. The study population included all librarians working in the libraries of Iran, Tehran and Shahid-Beheshti universities of medical sciences with at least a bachelor's degree in librarianship. Descriptive and analytical statistics were used to analyze the data by Spss24 software. Results: The status of using social media for marketing library services in libraries of Iran, Tehran and Shahid-Beheshti universities of medical sciences, based on 4P marketing mix, was as follows: in price components (cost-benefit) with an average of 2.4, location (social media) with an average of 2.36, product (library services) with an average of 2.29, and promotion components with an average of 2.27. Their level of use in all four components was relatively unfavorable. Conclusion: Due to the unfavorable level of using social media for marketing library services in these universities, it is necessary to encourage more effective planning to hold retraining and in-service courses in the areas of marketing, social media tools and content production in these media to encourage medical Librarians to know and use these tools in library services.